Meta-analysis of Vascular Imaging Features to Predict Outcome Following Intravenous rtPA for Acute Ischemic Stroke - Nogueira, Ricardo C.; Bor-Seng-Shu, Edson; Saeed, Nazia P.; Teixeira, Manoel J.; Panerai, Ronney B.; Robinson, Thompson G. (Frontiers in Neurology, 2016)
Background The present review investigated which findings in vascular imaging techniques can be used to predict clinical outcome and the risk of symptomatic intracerebral hemorrhage (sICH) in patients who underwent intravenous thrombolytic treatment. Methods Publications were searched, and the inclusion criteria were as follows: (1) published manuscripts, (2) patients with acute ischemic stroke managed with intravenous recombinant tissue plasminogen activator (rtPA), and (3) availability of imaging assessment to determine vessel patency or the regulation of cerebral blood flow prior to, during, and/or after thrombolytic treatment. Clinical outcomes were divided into neurological outcome [National Institutes of Health Stroke Scale (NIHSS) within 7 days] and functional outcome (modified Rankin score in 2–3 months). sICH was defined as rtPA-related intracerebral bleeding associated with any worsening of NIHSS. Results Thirty-nine articles were selected. Recanalization was associated with improved neurological and functional outcomes (OR = 7.83; 95% CI, 3.71–16.53; p < 0.001 and OR = 11.12; 95% CI, 5.85–21.14; p < 0.001, respectively). Both tandem internal carotid artery/middle cerebral artery (ICA/MCA) occlusions and isolated ICA occlusion had worse functional outcome than isolated MCA occlusion (OR = 0.26, 95% CI, 0.12–0.52; p < 0.001 and OR = 0.24, 95% CI, 0.07–0.77; p = 0.016, respectively). Reocclusion was associated with neurological deterioration (OR = 6.48, 95% CI, 3.64–11.56; p < 0.001), and early recanalization was associated with lower odds of sICH (OR = 0.36, 95% CI, 0.18–0.70; p = 0.003). Conclusion Brain circulation data before, during, and after thrombolysis may be useful for predicting the clinical outcome. Cerebral arterial recanalization, presence and site of occlusion, and reocclusion are all important in predicting the clinical outcome.